2012
DOI: 10.1177/0194599812464759
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of Hypoxia‐Inducible Factor–1α and Survivin in Laryngeal Carcinoma Tissue and Cells

Abstract: HIF-1α could be considered as an important regulator for the upregulation of survivin gene expression induced by hypoxia in LSCC cells, and both proteins could be regarded as 2 key predictors of malignant progression and metastasis of LSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
(44 reference statements)
3
23
2
Order By: Relevance
“…Following a review of the literature, only 13 studies on the topic of laryngeal carcinoma and HIF were identified (Table I). These studies all examined the expression of HIF-1α only, and none investigated HIF-1α mRNA expression levels from in vivo samples (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The current study is the first to present full quantitative data regarding the mRNA expression levels of HIF-1α and HIF-2α in laryngeal carcinoma samples, and is the first to report on the mRNA expression levels of HIF-3α in an in vivo study of a malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Following a review of the literature, only 13 studies on the topic of laryngeal carcinoma and HIF were identified (Table I). These studies all examined the expression of HIF-1α only, and none investigated HIF-1α mRNA expression levels from in vivo samples (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The current study is the first to present full quantitative data regarding the mRNA expression levels of HIF-1α and HIF-2α in laryngeal carcinoma samples, and is the first to report on the mRNA expression levels of HIF-3α in an in vivo study of a malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from the laryngeal carcinoma cells using TRIzol ® Reagent (Invitrogen; Thermo Fisher Scientific, Inc.) according to the manufacturer's protocols. Subsequently, the isolated RNA was reverse-transcribed into complementary DNA (cDNA) using the PrimeScript ® RT Reagent kit (Takara Bio, Inc., Otsu, Japan), as previously described (14). The primers used were as follows: MDR1 sense, 5'-CTT CAG GGT TTC ACA TTT GGC-3' and antisense, 5'-GGT AGT CAA TGC TCC AGT GG-3'; and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) sense, 5'-CAT CTT CCA GGA GCG AGA-3' and antisense, 5'-TGT TGT CAT ACT TCT CAT-3'.…”
Section: Methodsmentioning
confidence: 99%
“…6), indicating that although both HIF-1α and HIF-2α are involved in the regulation of laryngeal CSCs, HIF-1α may dominate. These findings may be helpful in explaining the relevant results from our recent study (34) where HIF-1α was highly expressed in laryngeal cancer tissues and significantly related to the clinical stage and lymph node metastasis, a possible explanation may be that advanced and metastatic cancer tissues contained a larger proportion of CSCs.…”
Section: Discussionmentioning
confidence: 55%